A review of malaria epidemiology and control in Papua New Guinea 1900 to 2021: Progress made and future directions - Cleary, Eimear; Hetzel, Manuel W.; Clements, Archie C. A. (Frontiers in Epidemiology, 2022)
The research and control of malaria has a long history in Papua New Guinea, sometimes resulting in substantial changes to the distribution of infection and transmission dynamics in the country. There have been four major periods of malaria control in PNG, with the current control programme having commenced in 2004. Each previous control programme was successful in reducing malaria burden in the country, but multiple factors led to programme failures and eventual breakdown. A comprehensive review of the literature dating from 1900 to 2021 was undertaken to summarise control strategies, epidemiology, vector ecology and environmental drivers of malaria transmission in PNG. Evaluations of historical control programmes reveal poor planning and communication, and difficulty in sustaining financial investment once malaria burden had decreased as common themes in the breakdown of previous programmes. Success of current and future malaria control programmes in PNG is contingent on adequate planning and management of control programmes, effective communication and engagement with at-risk populations, and cohesive targeted approaches to sub-national and national control and elimination.